Spatio-temporal expression of candidate genes for nectar spur development in Tropaeolum (Tropaeolaceae: Brassicales) (2023)
• Background and Aims: Tropaeolaceae (Brassicales) comprise ~100 species native to South and Central America. Tropaeolaceae flowers have a nectar spur, formed by a late expansion and evagination of the fused proximal region of the perianth (i.e. the floral tube). This spur is formed in the domain of the tube oriented towards the inflorescence axis, which corresponds to the adaxial floral region. However, little is known about the molecular mechanisms responsible for the evolution of spurs in Tropaeolaceae. • Methods: In this study, we examined the spatio-temporal expression of genes putatively responsible for differential patterns of cell division between the adaxial and abaxial floral regions in Tropaeolaceae. These genes include previously identified TCP and KNOX transcription factors and the cell division marker HISTONE H4 (HIS4). • Key Results: We found a TCP4 homologue concomitantly expressed with spur initiation and elaboration. Tropaeolaceae possess two TCP4 like (TCP4L) copies, as a result of a Tropaeolaceae-specific duplication. The two copies (TCP4L1 and TCP4L2) in Tropaeolum longifolium show overlapping expression in the epidermis of reproductive apices (inflorescence meristems) and young floral buds, but only TlTCP4L2 shows differential expression in the floral tube at early stages of spur formation, restricted to the adaxial region. This adaxial expression of TlTCP4L2 overlaps with the expression of TlHIS4. Later in development, only TlTCP4L2 is expressed in the nectariferous tissue of the spur. • Conclusions: Based on these results, we hypothesize that Tropaeolaceae TCP4L genes had a plesiomorphic role in epidermal development and that, after gene duplication, TCP4L2 acquired a new function in spur initiation and elaboration. To better understand spur evolution in Tropaeolaceae, it is critical to expand developmental genetic studies to their sister group, the Akaniaceae, which possess simultaneously an independent duplication of TCP4L genes and a spurless floral tube.